Evaluating Vocabulary Learning with the English With Tiffani App: A Qualitative Study of Student Perceptions and Pedagogical Outcomes - Nasution, Haikal Affakih; Daulay, Ernita (Universitas Negeri Semarang, 2024)
The qualitative study investigated the impact of the English With Tiffani App on vocabulary learning among students, against a backdrop of increasing reliance on digital tools in education. The objective was to evaluate the app's effectiveness as a Mobile Assisted Language Learning (MALL) tool and to understand student perceptions regarding its usage. Using a descriptive qualitative research methodology, data were collected through interviews with students who had used the app for vocabulary enhancement. The results revealed that students found the app beneficial for learning new vocabulary and engaging due to its gamified elements and user-friendly interface. It was concluded that the English With Tiffani App significantly aids in vocabulary acquisition, enhancing students' language learning experiences and outcomes. This study contributes to educational technology by providing empirical evidence on the advantages of gamification in language learning and by suggesting practical implications for incorporating similar digital tools in educational settings to improve student engagement and learning outcomes.